A Projec Report on Fog Computing Mitigating Inside Data Theft Attack in Cloud - KIRAN BHAT, UDAY KUMAR, MANJUNATH T N and PRASHANT DESHPANDE (2012)
INTERNAL GUIDE: G SIVAGAMA SUNDARI, MVJCE
Keywords: Fog Computing Mitigating Inside Data Theft Attack in Cloud